2013
DOI: 10.1371/journal.pone.0068608
|View full text |Cite|
|
Sign up to set email alerts
|

The Transcriptomic Basis of Oviposition Behaviour in the Parasitoid Wasp Nasonia vitripennis

Abstract: Linking behavioural phenotypes to their underlying genotypes is crucial for uncovering the mechanisms that underpin behaviour and for understanding the origins and maintenance of genetic variation in behaviour. Recently, interest has begun to focus on the transcriptome as a route for identifying genes and gene pathways associated with behaviour. For many behavioural traits studied at the phenotypic level, we have little or no idea of where to start searching for “candidate” genes: the transcriptome provides su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 72 publications
3
38
0
1
Order By: Relevance
“…2, the distribution of unigenes annotated as molecular function showed that the genes expressed in the antennae were primarily related to binding activity (6545 unigenes, 46.19%), whereas 1236 (8.72%) of the unigenes were involved in transporter activity. Similar trends in GO annotation were also observed in the transcriptomic analyses of C. vestalis and N. vitripennis (Nishimura et al, 2012;Pannebakker et al, 2013).…”
Section: Overview Of Antennal Transcriptome Of Sclerodermus Spsupporting
confidence: 77%
“…2, the distribution of unigenes annotated as molecular function showed that the genes expressed in the antennae were primarily related to binding activity (6545 unigenes, 46.19%), whereas 1236 (8.72%) of the unigenes were involved in transporter activity. Similar trends in GO annotation were also observed in the transcriptomic analyses of C. vestalis and N. vitripennis (Nishimura et al, 2012;Pannebakker et al, 2013).…”
Section: Overview Of Antennal Transcriptome Of Sclerodermus Spsupporting
confidence: 77%
“…Female Nasonia are synovigenic, meaning that they emerge from their host with a partial complement of mature eggs and can reproduce right away, but will continue to produce eggs as long as they consume enough protein (Pannebakker et al, 2013). Therefore, the WPL gives first insight on the parasitization ability of polyploid parasitoid females.…”
Section: Discussionmentioning
confidence: 99%
“…However, females produce less-biased, or even male-biased, sex ratios, depending on the number of other females (foundresses) ovipositing together on a host and the relative clutch sizes produced by those females (Hamilton 1967;Werren 1980;). While we have a detailed understanding of the information used by female Nasonia during sex allocation (e.g., Werren 1980Werren , 1983King et al 1995;Shuker and West 2004;Shuker et al 2005Shuker et al , 2006aBurton-Chellew et al 2008), we have only a rudimentary understanding of the genetic basis of sex allocation (Pannebakker et al 2008(Pannebakker et al , 2011(Pannebakker et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…First, the sex allocation machinery, from the perception of LMC cues (e.g., Shuker and West 2004) to the control of fertilization, could be independent of any influence of DNA methylation. We have recently shown that facultative sex allocation in N. vitripennis is not associated with changes in gene expression, even though oviposition itself is (Pannebakker et al 2013 A, The optimal sex ratios under local mate competition for maternally inherited alleles (blue curve) and paternally inherited alleles (red curve) for a haplodiploid with female control of sex allocation (the black curve is the local mate competition prediction with no genomic conflict; equations given in Wild and West 2009). B, Females treated with 5-aza-2 0 -deoxycytidine (red bars) produce slightly less female-biased sex ratios than controls (blue bars).…”
Section: Introductionmentioning
confidence: 99%